2002
DOI: 10.1021/ac011183q
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enumeration of Respiratory Viruses

Abstract: Virus detection and enumeration has become increasingly important in fields ranging from medicine and biotechnology to environmental science. Although there are a wide variety of techniques that can be used to count viruses, there is demand for a rapid and more accurate means for virus enumeration. In this work, the performance of a flow cytometer that was designed and custom-built specifically for rapid detection of single viruses was evaluated. The instrument, designated a single nanometric particle enumerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…This system achieved the multicolor detection of hydrodynamically focused fluorescent particles and nucleic acid labeled fungus. In another study, a combination of an Arlaser and a photomultiplier tube (PMT)-based optical system were used to produce a single nanometric particle enumerator with a diffraction-limited spot size of ,0.5 mm and a probe volume of ,8 fL [58]. With this system, it was demonstrated that single nanoparticles with diameters as small as 26 nm could be detected without sophisticated detectors and electronics.…”
Section: Optical Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system achieved the multicolor detection of hydrodynamically focused fluorescent particles and nucleic acid labeled fungus. In another study, a combination of an Arlaser and a photomultiplier tube (PMT)-based optical system were used to produce a single nanometric particle enumerator with a diffraction-limited spot size of ,0.5 mm and a probe volume of ,8 fL [58]. With this system, it was demonstrated that single nanoparticles with diameters as small as 26 nm could be detected without sophisticated detectors and electronics.…”
Section: Optical Detectionmentioning
confidence: 99%
“…In addition to an analysis of suspended cell populations (e.g., red blood cells, platelets, lymphocytes, monocytes, and granulocytes), Ferris et al [58] also performed viral analysis, and demonstrated the rapid enumeration of adenovirus, respiratory syncytial virus, and influenza virus. Their instrument was able to complete an analysis within 1 h, and thereby, possesses clear advantages over conventional viral analysis procedures, such as, cell culture techniques, plaque assays, or tunneling electron microscopy.…”
Section: Biomedical Informationmentioning
confidence: 99%
“…We set up the flow cytometer to be triggered by the fluorescent label of the MNP and tested different flow rates to acquire samples. We chose a flow rate below 150 events per second, which, on the basis of earlier reports (19), we expected (and proved below) to resolve individual particles. We used a gate of fluorescence width versus height to exclude aggregates ( Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that most of the cells survived the electric field used to effect their transport and could be successfully detected at throughput rates of between 30 and 85 cells per second. Ferris et al [38] combined a capillary microchannel with an AR-laser and a PMT-based optical system to accomplish a single nanometric particle enumerator for the detection of fluorescently labeled virus cells. The resulting system was inexpensive compared to commercial flow cytometers, had no requirement for sophisticated detectors or electronics, and was capable of detecting single nanoparticles with diameters as little as 26 nm.…”
Section: Introductionmentioning
confidence: 99%